(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the training needs of feamle teachers of Omani students with learning disabilities in the light of the 21st century skills. The descriptive method was used in the study. The sample of the study consisted of 272 female teachers. These teachers responded to a questionnaire that consisted of 28 items coverring the following three domains: learning and innovation skills, life and career skills, and digital literacy skills. The results showed that the level of the training needs of the teachers of students with learning disabilities was moderate. The results also showed that there were no significant differences due to specialization and academic qualification., while there were differences in the domain of life and career skills in relation to the teaching experience variable in favor of female teachers (10 years or less). The study recommended the necessity of integrating the 21st century skills in the programs of preparing learning disabilities teachers in universities and conducting in-service training programs based on these skills for teachers of students with learning disabilities in Oman.